Time trend and costs of hospitalizations with diabetes mellitus as main diagnosis in the Brazilian National Health System, 2011 to 2019 - Ludmilla Ferreira da Costa; Taisa Lara Sampaio; Lenildo de Moura; Roger dos Santos Rosa; Betine Pinto Moehlecke Iser (Ministério da Saúde do Brasil, 2024)
ABSTRACT Objective To analyze the diabetes mellitus (DM) temporal trend and hospitalization costs in Brazil, by region, Federative Units (FUs) and population characteristics, from 2011 to 2019. Methods This was an ecological study with data from the Hospital Information System, analyzing the annual trend in hospitalization rates for DM according to sex, age, race/skin color and region/FU by Prais-Winsten generalized linear regression. Results A total of 1,239,574 DM hospitalizations were recorded in the country and the hospitalization rates was 6.77/10,000 inhabitants in the period. The DM hospitalization rates trend was falling for both sexes and in most regions, while it was rising in the younger population and for length of stay (average 6.17 days). Total expenditure was US$ 420,692.23 and it showed a rising trend. Conclusion The temporal trend of hospitalization rates due to DM was falling, with differences according to region/FU and age group. Average length of stay and expenditure showed a rising trend.